Evaluation of Trypanocidal and Antioxidant Activities of a Selected Series of 3-Amidocoumarins - Matsuhiro-Yamamoto, B; Matsuhiro-Yamamoto, B; Moncada-Basualto, M (Bentham Science Publishers B.V., 2018)
Background: Neglected diseases are becoming more prevalent due to globalization. This has inspired active research in the development of new drugs for the treatment of parasitic diseases such as Chagas disease. Objectives: With the aim of finding new trypanocidal agents, we report the in vitro evaluation of a new series of 3-amidocoumarins with or without hydroxyl substituents at position 4 of the coumarin ring. Methods: Electrochemical and biological assays were performed in order to assess the antioxidant and trypanocidal potential of these compounds and to better understand the mechanisms involved in their activity. Results: Most of the studied compounds showed high trypanocidal activity against both epimastigote and trypomastigote forms, with IC50 values in the low micromolar range. Some of them have greater activity and selectivity than the reference compound, nifurtimox. Conclusion: Compound 2 is the most active of this series, being also non-cytotoxic against murine RAW 264.7 macrophages. Electrochemical and radical scavenging experiments were carried out, providing new information about the profile of the best derivatives, and the potential therapeutic application of the new 3-amidocoumarins. © 2018 Bentham Science Publishers.